CULTURES OF ORALITY AND PERFORMATIVITY IN THE PERFORMING ART TRADITION OF PURULIA CHHAU - Kumar, Maheshwar; Nayak, Amarjeet; Swain, Pranaya Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purulia Chhau, a folk, tribal, martial, masked dance-drama form of Eastern India, is performed over generations orally. Having no written performance text available, all the actions of Purulia Chhau, such as gestures, postures, dance movements and so on are materialized through the various performative utterances by the vocalist, who provide the storyline of the Chhau repertoires; musicians, who bring musical tempo into dance movements; and the dancers, who are dressed in big headgear masks and dynamic costumes enact the actual Chhau performances. Referring to the social and cultural perspectives and employing a qualitative approach as the primary methodological tool, the present paper, at the first level, seeks to explore how the cultures of orality exists in Purulia Chhau tradition and critically evaluates three Chhau repertoires with their contextual significance. It also examines how this folk-dance form manifests cultural values, shared beliefs and customs, and represents a unique cultural identity among the concerned people. At the second level, the paper analyses how the idea of performativity works on its reflexive level in Purulia Chhau and creates meaning to the audience. It also emphasizes on the performative procedure invoked and executed by all the performers correctly and completely.